Automatic Generation of Software Tools Using a Language Grammar - Parker, Glenn A. (SoutheastCon 2018, 2018)
This paper discusses early results for automatic generation of software tools from interface definitions described by Interface Definition Language (IDL). Modern distributed systems and System-of-Systems designs often employ IDL to define messages that may be exchanged during operation, and these definitions are then used in the design and testing of individual subsystems. A method is presented here for using a popular domain-specific language compiler in conjunction with IDL definitions to generate test tools for a distributed system. This approach can dramatically speed development and decrease cost in systems where the interface definition is subject to change.